2019
DOI: 10.1145/3343195
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Women's Persistence in Computer Science- and Technology-Related Majors from High School to College

Abstract: While demand for computer science and information technology skills grows, the proportion of women entering computer science (CS) fields has declined. One critical juncture is the transition from high school to college. In our study, we examined factors predicting college persistence in computer science- and technology-related majors from data collected from female high school students. We fielded a survey that asked about students’ interest and confidence in computing as well as their intentions to learn prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 20 publications
2
15
0
3
Order By: Relevance
“…For example, Wang et al [58] found that regardless of the exposure (unstructured or structured), high school girls who had engaged with computer science classes were more likely to consider computer science-related degrees than girls with no such experience. Along the same lines, Weston, Dubow and Kaminsky [61] found that among the main predictors of women persistence in computer science was the programming experience in high school. A lot of other researchers highlighted previous knowledge, skills and participation in computer science practices as pre-requisite for persistence in computer science fields (e.g., [1], [60]).…”
Section: How Can Inequalities In Computer Sciencementioning
confidence: 83%
“…For example, Wang et al [58] found that regardless of the exposure (unstructured or structured), high school girls who had engaged with computer science classes were more likely to consider computer science-related degrees than girls with no such experience. Along the same lines, Weston, Dubow and Kaminsky [61] found that among the main predictors of women persistence in computer science was the programming experience in high school. A lot of other researchers highlighted previous knowledge, skills and participation in computer science practices as pre-requisite for persistence in computer science fields (e.g., [1], [60]).…”
Section: How Can Inequalities In Computer Sciencementioning
confidence: 83%
“…2) Social stigma: Women in mechanical engineering may be viewed as being rude because they work in the construction field with men (Strachan et al, 2018). 3) Academic stereotypes: peers, teachers, parents, school counsellors, and relatives may suggest that women should pursue liberal arts majors instead of vocation-oriented subjects, such as engineering and the sciences (Weston et al, 2020). 4) Earning differences: Even when both men and women hold the same position and title, women usually receive a lower salary and fewer benefits than their male co-workers do (White, 2018).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…They observed that adopting advanced network technologies for teaching can support the transformation and pave the way for in-depth construction of high-quality education (Crues et al, 2018). Also, Abu Zohair (2019) notes that accurate data analysis has not only become essential for improving the students' performance and experience (Crues et al, 2018;Kori et al, 2018;Weston, Dubow, & Kaminsky, 2019) but it also serves as a mechanism for elevating the university's ranking and reputation. The results of the study by Abu Zohair (2019) show that support vector machines or algorithms can be used to train and analyze the readily available datasets to produce acceptable learning-processclassification accuracy and reliability test rates (Liao et al, 2019).…”
Section: Information Technologies For Quality Education and Innovationmentioning
confidence: 99%
“…On the other hand, Wen et al (2014) investigate what sentiment analysis can tell us about the students' opinions with regards to the learning experiences (Crues et al, 2018). Notably, Moshinskie (2001) states that it is essential to monitor the students' feelings or emotions because learners with a positive attitude have been seen as more confident and motivated to learn (Weston et al, 2019). Besides, considering the students as consumers of the educational systems and curricula is one of the main reasons to use digital learning strategies as a way to personalize learning experiences (Munro, 2018;Romero, Saucedo, Caliusco, & Gutiérrez, 2019).…”
Section: Sentiment Analysis For Educational Process Innovation and Damentioning
confidence: 99%